2022
DOI: 10.1075/jslp.21022.mer
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal impact of self-reflection and integrated pronunciation instruction on L2 French learners’ production of /y/ and /u/

Abstract: Although pronunciation can be fostered through explicit instruction, instructors need practical strategies to support their learners’ pronunciation (Darcy, 2018; Derwing, 2018; Derwing & Munro, 2015; Levis, 2018). Additionally, “researching longitudinal development of L2 learners [pronunciation] is essential to understanding influences in their success” (Derwing & Munro, 2013, p.163). This three-semester-long experimental quantitative study on 72 French learners examined whether self-reflection (open-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Past research has shown that pronunciation instruction has a significant impact on learners' pronunciation improvement (Derwing, 2018; Lee et al, 2015; Levis & Wu, 2018; Martin, 2020a, 2020b; Meritan, 2020; Meritan & Mroz, 2019; Saito & Plonsky, 2019). Many studies have been conducted on learners in an ESL context (e.g., Darcy, 2018; Venkatagiri & Levis, 2007) and on learners in a naturalistic or immersion settings (e.g., Bergeron & Trofimovich, 2017; Kennedy et al, 2014), with learners benefiting from pronunciation instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Past research has shown that pronunciation instruction has a significant impact on learners' pronunciation improvement (Derwing, 2018; Lee et al, 2015; Levis & Wu, 2018; Martin, 2020a, 2020b; Meritan, 2020; Meritan & Mroz, 2019; Saito & Plonsky, 2019). Many studies have been conducted on learners in an ESL context (e.g., Darcy, 2018; Venkatagiri & Levis, 2007) and on learners in a naturalistic or immersion settings (e.g., Bergeron & Trofimovich, 2017; Kennedy et al, 2014), with learners benefiting from pronunciation instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have also investigated pronunciation gains of intermediate to advanced French learners in phonetics or pronunciation courses (e.g., Inceoglu, 2019, 2021; Lappin‐Fortin & Rye, 2014; Sturm, 2013a, 2013b; Violin‐Wigent, 2014). However, very few studies have investigated integrated explicit pronunciation instruction (or lack thereof) at the beginner and/or intermediate level in French classrooms (Meritan, 2020; Miller, 2012; Sturm, 2019, 2021). Miller (2012) explored the effectiveness of two different pronunciation teaching approaches on beginner French learners.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, training in self‐reflection and self‐assessment appears to lead to more convergence between learners' self‐assessments and teachers' evaluations (Babaii et al, 2016; Chen, 2008; see also Meritan & Mroz, 2019). Similarly, repeated self‐assessment seems to impact learners' language performance positively, such that those who self‐assess their speech over time improve in various dimensions of speech, including fluency, pronunciation, and connected speech processes (de Saint Léger 2009; Kissling and O'Donnell 2015), likely through increased awareness of these dimensions (for empirical work linking L2 learners' pronunciation development to measures of self‐reflection and awareness, see Meritan, 2020; Meritan & Mroz, 2019; Sturm, 2013, 2019).…”
Section: Background Literaturementioning
confidence: 99%